KONTRIBUSI PENDAPATAN BURUH PANEN CV. NUSA JAYA TERHADAP PENDAPATAN PETANI KARET DI KECAMATAN AIR KUMBANG KABUPATEN BANYUASIN - Andrianto, Alip; Iskandar, Sutarmo; Kurniawan, Rahmat (Universitas Muhammadiyah Palembang, 2019)
ABSTRACT This research has conducted to find out about how much rubber farm income and labor contribution of harvesting CV. Nusa Jaya to the income of rubber farmers. This research aims to find out how much is the income of rubber farming and how much is the contribution to the harvest labor income of CV. Nusa Jaya to the income of rubber farmers. This research was conducted in the Air Kumbang District of Banyuasin District in November 2018 to January 2019. The research method used was Survey. The sampling method used was the purposive sampling method. The data collection method used in the study was direct observation and interviews with respondents using a list of questions prepared previously and data obtained from relevant institutions related to this study. To answer the first problem is how much rubber farming income. Meanwhile, to answer the second problem formulation, how much is the contribution of harvest labor income in the CV. Nusa Jaya, on the income of rubber farmers, the data obtained from the field are processed tabulating. The results showed that farmers' income from rubber farming averaged Rp. 20,088,769.3 / Lg / Year. And the average income of the sample farmers who worked as harvest laborers in the CV. Nusa Jaya averages Rp 39,666,161 / Year. As for the contribution of harvest workers’ CV. Nusa Jaya to the income of rubber farmers in the District of Air Kumbang, which is 66.78%.